Intellectualization of the economy as a factor in the development of industrial enterprises - Marchuk, L. S. (WSEH, 2020)
In today's conditions, the growth of the competitive environment and globalization processes significantly affect the state of the world economy, its development is determined by the level of use of intellectual potential. The most important and significant process is the intellectualization not only of the economy but also of production, which in turn is responsible for the high qualification of staff and continuous improvement. If we consider the intellectual potential at the macroeconomic level in economic globalization processes, it acts as the main factor determining the country's place in the world economic arena.
Keywords: intellectual potential; technologies; staff; modern economic processes